2019
DOI: 10.1016/j.comgeo.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Spectral concentration and greedy k-clustering

Abstract: A popular graph clustering method is to consider the embedding of an input graph into R k induced by the first k eigenvectors of its Laplacian, and to partition the graph via geometric manipulations on the resulting metric space. Despite the practical success of this methodology, there is limited understanding of several heuristics that follow this framework. We provide theoretical justification for one such natural and computationally efficient variant.Our result can be summarized as follows. A partition of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Beyond these good properties of Laplacian eigenmaps classically studied in the literature, one important remaining question is whether Laplacian eigenmaps preserve the clusters through the transportation of the high-dimensional (possibly manifold supported) distribution on the low-dimensional space. In the case where the clusters are well separated, it is a well known fact that clusters can be recovered from the sign patterns in the components of the eigenvectors of the Laplacian matrix [13], [14]; see also [15]. Understanding spectral clustering through the lens of statistical phase transition phenomena under a very different model has been the focus of extensive research activity in recent years, via the analysis of the stochastic block model [16,17] and its generalisations to e.g.…”
Section: Challenges and Achieved Resultsmentioning
confidence: 99%
“…Beyond these good properties of Laplacian eigenmaps classically studied in the literature, one important remaining question is whether Laplacian eigenmaps preserve the clusters through the transportation of the high-dimensional (possibly manifold supported) distribution on the low-dimensional space. In the case where the clusters are well separated, it is a well known fact that clusters can be recovered from the sign patterns in the components of the eigenvectors of the Laplacian matrix [13], [14]; see also [15]. Understanding spectral clustering through the lens of statistical phase transition phenomena under a very different model has been the focus of extensive research activity in recent years, via the analysis of the stochastic block model [16,17] and its generalisations to e.g.…”
Section: Challenges and Achieved Resultsmentioning
confidence: 99%
“…These approaches are less accurate, however [2,25]. The approximability of temporal versions of k-means clustering and its variants was studied by Dey et al [10].…”
Section: Return Truementioning
confidence: 99%
“…The parameterized complexity of the local approach of aggregating clusterings into one has been studied for multi-layer [70,71] and temporal graphs [16,17]. The approximability of temporal versions of k-means clustering and its variants was studied by Dey et al [72].…”
Section: Related Workmentioning
confidence: 99%
“…They also showed that, if a graph satisfies 𝜆 k+1 > 0 , there is a polynomial time algorithm that outputs a -way partition of the graph that is a (Ω( 2 k+1 ∕k 4 ), O(k 6 √ k ))-clustering where 1 ≤ ≤ k . Dey et al (2019) developed a greedy algorithm that partitions the node set of a graph into clusters with a large inside conductance and small outside conductance. They showed that, if there is a large gap between k and k+1 , the output of the algorithm is close to a (Ω( k+1 ∕k), O(k 3 √ k ))-clustering.…”
Section: Related Workmentioning
confidence: 99%